Education and Responsibilities of Stakeholders: Understanding Language Education Policies and Stakeholder Roles in Rural Colombia (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Drawing on the idea of strategy allocation, this examination researches how unique training partners in a rustic district of Colombia see unknown dialect instruction strategies, and how these discernments shape the manner in which they reproduce these changes at the ground level. Adding to the field of language strategy examination in Colombia and abroad, discoveries in this investigation not just give information on unknown dialect policymaking measures in country zones in Colombia, yet in addition shed light on the dynamic pretended by various partners in the persistent diversion and apportionment of language schooling changes.